AB0074 Alkylating Agents Enhance Interleukin-10 Secretion from B Cells via P38 MAP Kinase Activation. (10th June 2014) - Lu, L.; Morita, A.; Yoshimoto, K.; Kameda, H.; Takeuchi, T.
Abstract : Background: Alkylating agents such as melphalan and bendamustine are commonly used in the treatments of tumors, especially hematologic malignancies. However, the exact mechanisms of their actions to B cells have not been fully clarified. Objectives: To investigate the effects of these alkylating agents on B cell functions, and to explore a possible clinical application of the agents to autoimmune diseases. Methods: We used two alkylating agents, melphalan and bendamustine, which are inhibitors of DNA replication. We also used methotrexate (MTX), which is another inhibitor of DNA replication and commonly used in rheumatoid arthritis therapies. A human B cell line, Ramos, was cultured in the presence of various concentrations of melphalan, bendamustine or MTX for four days. The proliferation of the cells was analyzed by XTT assay and the secretions of IgM and cytokines by the cells were measured by ELISA. The cells and cellular mRNA were collected for FACS analysis and quantitative RT-PCR, respectively. Nuclear extracts were prepared from the cells and Electrophoresis Mobility Shift Assay (EMSA) was employed for detection of DNA-binding capacity. Results: The proliferation of Ramos cells was significantly inhibited by melphalan (2.5-20 μM), bendamustine (25-100 μM) or MTX (0.1-20 μM) in a dose-dependent manner. Concordantly, IgM secretion from Ramos cells was significantly inhibited at these concentrations by up to 70%. Interestingly, however, the production and secretion of interleukin-10 (IL-10) from Ramos were dramatically (>10-fold) increased upon treatment with these drugs. Melphalan and bendamustine induced higher levels of IL-10 than MTX. Moreover, we found that both melphalan and bendamustine enhanced the activation of p38 MAP kinase. Inhibition of p38 MAP kinase by its specific inhibitor led to the abrogation of drug-induced IL-10 production. EMSA revealed that Sp1 was the downstream transcription factor involved in p38 MAP kinase activation by all three drugs (Fig. 1 ). Conclusions: P38 MAP kinase-Sp1 pathway plays a crucial role in IL-10 production from B cells induced by alkylating agents. Our results suggest that cessation of cell division via inhibition of DNA replication induces IL-10 production. MTX may exert its therapeutic effects partly via immunosuppressive effects of IL-10. Our results also suggest that alkylating agents provide a therapeutic tool for autoimmune diseases through anti-inflammatory effects of IL-10. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3144